HEGEMONI KEKUASAAN DALAM NOVEL PUSPABANGSA KARYA KARIM NAS: Array - Asri, Tisatun; Irma, Cintya Nurika (DIALEKTIKA JURNAL PENDIDIKAN BAHASA INDONESIA, 2022)
This study aims to describe the hegemony of power in the novel Puspabangsa by Karim Nas. This type of research is a qualitative research with a descriptive approach. Data collection techniques were carried out by reading and note-taking techniques. Data analysis techniques in this study using data analysis techniques according to Miles and Huberman which include, data collection, data reduction, data presentation, and drawing conclusions. The results show that the hegemony of power contained in the Puspabangsa novel is divided into the areas of civil society and political society, with the hegemony of political society being the most common. Hegemony in civil society is carried out in citizen networks, Bandar Suci (temples), and schools, while hegemony of power in the area of ​ political society is carried out by the police, committees, high- ranking groups, Panditautama, and the council of consuls. Hegemony in the area of ​ civil society shows that the hegemony of power in the Puspabangsa novel is obtained from the results of consensus or agreement. Then, in political society, it shows that hegemonic actors actually use power a lot.